The impact of body composition and systemic inflammatory markers on postoperative complications in early-stage cervical cancer - Ding, Lipeng; Li, Shuangxi; Jin, Zhuanmei; Yao, Changyu; Zhang, Taohua; Yuan, Wenzhen (Frontiers in Oncology, 2026)
ObjectivePatients with cancer often present with alterations in body composition and systemic inflammation. Guided by this observation, we sought to determine whether these factors are associated with postoperative complications in early-stage cervical cancer.MethodsIn this retrospective cohort study, we analyzed data from 223 patients with early-stage cervical cancer treated at our center between July 2018 and December 2021.Postoperative complications were graded using the Clavien-Dindo classification. Systemic inflammatory markers were calculated from hematological parameters, while body composition indices were derived from computed tomography (CT) images at the third lumbar vertebra (L3) level and patient’s height. Group comparisons were performed using the χ² test, independent samples t-test, or Mann-Whitney U test, as appropriate. Binary logistic regression was applied to identify independent predictors of complications and conduct to sensitivity analysis to verify the robustness of the model.ResultsPreoperative CT scans and hematological tests were performed a mean of 3.4 and 4.1 days before surgery, respectively. Postoperative complications were predominantly Grade 1 (n=124, 55.6%), followed by Grade 2 (n=69, 30.9%) and Grade 3 (n=30, 13.5%). No complications ≥ Grade 4 were observed. Patients with complications ≥ Grade 2 were more likely to undergo open surgery, present with larger tumors, exhibit lower skeletal muscle index (SMI) and prognostic nutritional index (PNI), higher visceral adipose tissue index (VATI), as well as greater intraoperative blood loss, lower preoperative and postoperative albumin levels, increased thrombotic risk, and longer hospital stays. Multivariate analysis identified that a higher complication grade (≥Grade 2) was significantly associated with low SMI (OR = 0.34, 95% CI = 0.18–0.64, P < 0.001), high VATI (OR = 1.04, 95% CI = 1.02–1.06, P < 0.001), and low PNI (OR = 0.91, 95% CI = 0.84–0.98, P = 0.008). No significant associations were found with IMATI, SATI, or systemic inflammatory markers (NLR, PLR, LMR, NPR, SII). After conducting sensitivity analyses on the key findings, the results remained robust.ConclusionSarcopenia, visceral adiposity, and low PNI are independently associated with a higher risk of clinically significant postoperative complications in patients with early-stage cervical cancer.